ANALISIS KEKERASAN NONVERBAL PADA CERPEN SIMPUL TANAH DALAM CERITA DARI BRANG WETAN KARYA DADANG ARI MURTONO - Elviani, Nandah; Maolida, Dila Hibatun; Irma, Cintya Nurika (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2024)
This research aims to analyze the problem of social action in the short story Simpul Tanah by Dadang Ari Murtono. The method used in this research is qualitative descriptive method. This research is a type of qualitative research. The source of this research is Simpul Tanah short story. The data collection techniques used are reading and recording techniques. The data in this study were analyzed using a literary sociology approach. This literary work discusses the analysis of open and closed nonverbal violence in the short story Simpul Tanah in the story of Brang Wetan by Dadang Ari Murtono. The results showed that there are several forms of nonverbal violence contained in the short story, such as open violence such as a fight carried out by Sarip he did not hesitate to carry out his actions by slashing Paidi's neck, and closed violence such as threatening someone's behavior such as a fight carried out by the main character Sarip and Paidi which was planned by Sarip's uncle to Paidi so that his nephew was killed, and if successful then Paidi could marry his daughter. Keywords: nonverbal violence, social action, short story, sociology